STUDENTS 'LANGUAGE LEVELS IN COST CUTTATES, TANGERANG, BANTEN ENVIRONMENT - Jatut Yoga Prameswari; Rahmawati Rahmawati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: Language is an important and primary communication tool in daily life. Basically speaking is not only about delivering messages from the speaker to the listener. But, language is also related to diction, politeness, and attitude. In the era of globalization and sophisticated technology, sometimes it makes the speakers forget important things in the process of communicating or speaking. This is certainly related to the culture that developed in this country, Indonesia. The ability to speak is an important part of communication. This is because we have a culture and customs background that uphold the norms of politeness. The politeness of the language at this time, especially among adolescents has begun to be set aside, even some of them no longer care about it. Need to be held and conducted politeness research on students in the boarding environment. It is hoped that this research will provide a solution to the impoliteness of students in the language of the communication process. In general, these violations are caused by three factors, namely language ability, ability to understand context, and closeness. The situation above is also felt by the boarding house owner who is inhabited by students. The research method used is a qualitative method with a case study approach. Bassey (1999: 25) states that "Case study methods involve the collection and recording of data about a case or case ..." This statement can be interpreted that the case study methods include the collection and recording of data about one case or more. From the findings above, the results obtained for politeness of language by 46% and language impoliteness of 53%. Based on the results of these calculations it can be concluded that the communication or language process between boarders (students) and boarding owners is classified as impolite. The figure of 53% results of language impoliteness can occur by several factors, including the sense of closeness with the owner of the boarding house, the wrong choice of diction, and the language style used by the occupants of the boarding house.Keywords: politeness language, language, students